Application of PTCDA / Ti3C2Tx MXene as negative electrode material of aqueous manganese ion battery

By using PTCDA/Ti3C2TxMXene material as the negative electrode material in aqueous manganese ion batteries, the problem of side reaction of manganese anode is solved, high cycle stability and Coulomb efficiency are improved, and the overall performance of the battery is significantly improved.

CN119650887AActive Publication Date: 2025-03-18ANHUI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411626888.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Manganese anode is prone to side reactions in aqueous solution batteries, resulting in manganese oxidation and spontaneous corrosion reactions, limiting the battery's Coulomb efficiency and cycle stability.

Method used

The composite material is synthesized by electrostatic self-assembly and coated on the electrode as the negative electrode of the aqueous manganese ion battery.

Benefits of technology

It significantly improves the electron conductivity and ion diffusion coefficient of the electrode, achieves fast ion diffusion kinetics and high cycling stability, improves the reversible specific capacity and long cycle life of the battery, avoids corrosion reactions, and enhances Coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650887A_ABST
    Figure CN119650887A_ABST
Patent Text Reader

Abstract

The invention provides a composite material PTCDA / Ti < 3 > C < 2 > T < x > MXene negative electrode applied to an aqueous manganese ion battery. Wherein the MXene has a stable two-dimensional layered structure, the PTCDA can be used for storing manganese ions during charging and discharging, and when the PTCDA is intercalated into the MXene, the PTCDA and the MXene interact with each other, so that the electronic conductivity and the ion diffusion coefficient of the electrode are remarkably improved, and the electrochemical performance of the electrode is improved. Therefore, rapid ion diffusion kinetics and high cycle stability in the negative electrode of the rechargeable water-based manganese ion battery are realized, so that the electrode has high reversible specific capacity and long cycle life, and shows excellent electrochemical performance. When the PTCDA / Ti3C2Tx MXene negative electrode is applied to an aqueous manganese ion battery, the high reversible capacity of 199mAh g <-1 > is provided under the current density of 0.5 A g <-1 >, the excellent cycling stability is achieved, and the capacity retention rate reaches 82% after 1000 times of charging and discharging cycles under the current density of 10A g <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aqueous manganese ion batteries, and specifically relates to a PTCDA / Ti3C2T3O4 battery composed of MXene and organic materials. x MXene materials and their applications in negative electrode materials for aqueous manganese ion batteries. Background Art

[0002] With the popularization of electric vehicles and the construction of smart grids, the importance of energy storage systems (ESSs) has become increasingly prominent. Among various energy storage systems, aqueous batteries are regarded as the optimal solution to balance cost-effectiveness, safety and energy demand due to their unique advantages such as high safety, low toxicity, easy manufacturing, low cost, environmental protection and high ionic conductivity. However, aqueous solution batteries still face many technical challenges on the road to commercialization, especially the limitations of output voltage and power density, which have become a bottleneck restricting their further development. To overcome this dilemma, the key lies in the discovery and development of new electrode materials or new battery systems with excellent performance. This is not only the core of promoting technological innovation of aqueous solution batteries, but also a key factor in achieving their large-scale commercial application. Although the use of high-performance electrode materials is indeed crucial, in the development of aqueous solution batteries, the exploration and application of new electrode systems is of greater significance. This is because it not only improves the performance of materials, but also is a key step in promoting the overall development of aqueous solution battery technology.

[0003] Among various battery systems, manganese metal has shown great potential in the field of aqueous solution batteries due to its unique physical and chemical properties. Manganese is expected to achieve higher energy density during the charge and discharge process. In addition, its low cost and non-toxic properties meet the requirements of sustainable development and environmental protection. Despite its many advantages, manganese still faces challenges when used as an anode material. During the charge and discharge process, the manganese anode is prone to side reactions with the electrolyte, leading to problems such as manganese oxidation and spontaneous corrosion reactions. These problems limit the coulombic efficiency (CE) and cycle stability of the battery. Coulombic efficiency is a key indicator for evaluating the energy conversion efficiency of the battery and directly affects its actual performance. At the same time, cycle stability is crucial for evaluating the battery life and performance stability, and is the key to ensuring the long-term stable operation of the battery. Therefore, solving the side reaction problem of the manganese anode and improving its coulombic efficiency and cycle stability have become urgent needs for the application of manganese metal in the field of aqueous solution batteries. Summary of the invention

[0004] The object of the present invention is to provide a PTCDA / Ti3C2T xThe application of MXene materials as negative electrode materials for aqueous manganese ion batteries, and the construction of a highly stable aqueous manganese ion battery. The present invention is based on the research of composite materials composed of organic materials and MXene as negative electrode materials for aqueous manganese ion batteries. Since manganese metal has a high HOMO energy level, it is very easy to undergo side reactions such as hydrogen evolution and oxygen evolution when used as a negative electrode material, which in turn causes serious corrosion problems and seriously affects the overall performance of the battery. The overall electrochemical performance of the battery is enhanced by replacing the traditional manganese metal negative electrode. Specifically, the present invention is implemented using the following technical solutions: On the one hand, the PTCDA / Ti3C2T x The application of MXene as a negative electrode material for aqueous manganese ion batteries adopts a method comprising the following steps: PTCDA / Ti3C2T x MXene is made into a slurry and coated on an electrode and dried as a negative electrode of a battery; wherein the PTCDA / Ti3C2T x MXene is synthesized by electrostatic self-assembly. x MXene material, because MXene is a stable two-dimensional layered structure, when PTCDA is intercalated into MXene, the interaction between PTCDA and MXene makes the composite structure more stable. The electrode can use graphite paper as a substrate, the coating area of ​​the active material on the graphite paper is 1cm×1cm, the drying temperature is 45-60℃, PTCDA / Ti3C2T x The optimal MXene loading is 0.5-1 mg, and the optimal drying time is 1-2 hours.

[0005] Preferably, for the above-mentioned application, PTCDA / Ti3C2T x MXene is prepared by the following method: Step (1): PTCDA raw powder is mixed with dimethylformamide (DMF) and ultrasonicated for 10-40 minutes; Step (2): remove water from MXene / H2O by centrifugation at a speed of 6000-10000 rpm for 10-40 minutes, then mix DMF and MXene and shake them well, and centrifuge to remove DMF; then add DMF and MXene and mix them well, and centrifuge to remove DMF, and repeat the DMF treatment to fully remove water to obtain MXene / DMF; Step (3): ultrasonically disperse the products obtained in step (1) and step (2) to obtain a mixed solution, and vacuum filter, wash and dry the obtained mixed solution.

[0006] For the above-mentioned application, preferably, in the step (1), the ratio of the mass of the original PTCDA powder to the volume of DMF is 18-22:4-6, mg / mL; preferably 20:5, mg / mL.

[0007] For the above-mentioned application, preferably, in the step (2), the ratio of the mass of MXene in the MXene / H2O liquid to the volume of DMF added each time is 15-20:4-6, mg / mL; preferably 16:5, mg / mL.

[0008] For the above-mentioned application, preferably, the mass ratio of the original PTCDA powder to MXene is 2-8:2-8, preferably 5-7:3-5, and more preferably 6:4.

[0009] For the above-mentioned application, preferably, the filter membrane used for vacuum filtration in step (3) is a 0.22 μm nylon membrane, and the membrane is washed with deionized water and anhydrous ethanol for 3-5 times respectively, the drying temperature is 40-45°C, and the drying time is 1 hour.

[0010] For the above-mentioned applications, preferably, PTCDA / Ti3C2T x MXene is made into slurry by mixing PTCDA / Ti3C2T x MXene is mixed with acetylene black, polyvinylidene fluoride and NMP, and then oscillated in a vortex oscillator. More preferably, PTCDA / Ti3C2T x The mass ratio of MXene, acetylene black and polyvinylidene fluoride is (4~8):(1~3):(1~3). When PTCDA / Ti3C2T x When the mass of MXene powder is 15-25 mg, the volume of NMP is 500 μL.

[0011] On the other hand, the present invention also provides an aqueous manganese ion battery, which comprises PTCDA / Ti3C2T x MXene negative electrode, CuFe-TBA positive electrode and Mn 2+ Ion electrolyte; the PTCDA / Ti3C2T x MXene negative electrode is PTCDA / Ti3C2T x MXene is made into slurry and coated on the electrode and dried to prepare. x MXene is synthesized by electrostatic self-assembly. x The energy storage mechanism of MXene / Mn battery system is as follows Figure 5 As shown, CuFe-TBA is used as the positive electrode, PTCDA / Ti3C2Tx The full battery is composed of MXene as the negative electrode and 1 M MnSO4 as the electrolyte. Its energy storage mechanism is based on the Mn ion in PTCDA / Ti3C2T x Insertion / deinsertion of MXene anode (breaking and recovery of C=O bonds).

[0012] The composite material PTCDA / Ti3C2T x MXene negative electrode is used in aqueous manganese ion batteries. MXene has a stable two-dimensional layered structure, and PTCDA can be used to store manganese ions during charge and discharge. When PTCDA is intercalated into MXene, the interaction between PTCDA and MXene significantly improves the electronic conductivity and ion diffusion coefficient of the electrode, thereby achieving fast ion diffusion kinetics and high cycle stability in the negative electrode of rechargeable aqueous manganese ion batteries, which makes the electrode have high reversible specific capacity and long cycle life, showing excellent electrochemical performance.

[0013] The beneficial effects of the present invention are: (1) PTCDA / Ti3C2T x When MXene anode is used in aqueous manganese ion batteries, it can -1 At a current density of 199 mAh g -1 The high reversible capacity and excellent cycling stability at 10A g -1 At a current density of 1.5 %, the capacity retention rate reaches 82% after 1000 charge and discharge cycles.

[0014] (2) PTCDA / Ti3C2T x MXene anode, due to the interaction between PTCDA and MXene, achieves fast ion diffusion kinetics and high cycle stability of the rechargeable aqueous manganese ion battery anode.

[0015] (3) PTCDA / Ti3C2T x Compared with the traditional manganese metal anode, the MXene negative electrode does not undergo corrosion reaction, and hydrogen and oxygen evolution are more difficult to proceed, which makes the electrode have higher cycle stability, is more conducive to the storage of manganese ions, and has higher coulombic efficiency.

[0016] (4) Negative electrode material PTCDA / Ti3C2T x MXene is used in aqueous manganese ion batteries. Compared with traditional lithium ion batteries, it has the advantages of low cost, environmental friendliness, and high safety, and has great application potential in the field of electrochemical energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 a is PTCDA / Ti3C2T x SEM image of MXene, Figure 1 b is TEM image; Figure 2 The PTCDA / Ti3C2T x Rate curves of different ratios of PTCDA to MXene; Figure 3 The PTCDA / Ti3C2T x CV curves of MXene at different scan rates; Figure 4 The PTCDA / Ti3C2T x GCD curves of MXene at different current densities; Figure 5 The PTCDA / Ti3C2T x Schematic diagram of the energy storage mechanism of the MXene / manganese battery system; Figure 6 The PTCDA / Ti3C2T x MXene at 10A g -1 Charge and discharge cycle stability curve at current density.

[0018] Figure 7 The PTCDA / Ti3C2T x Comparison of the Coulombic efficiency of MXene and manganese metal. DETAILED DESCRIPTION

[0019] The following embodiments are further descriptions of the content of the present invention as an explanation of the technical content of the present invention, but the essential content of the present invention is not limited to the following embodiments. Ordinary technicians in this field can and should know that any simple changes or replacements based on the essential spirit of the present invention should fall within the scope of protection required by the present invention. Example 1

[0020] A composite material PTCDA / Ti3C2T x The method for preparing MXene as a negative electrode of an aqueous manganese ion battery comprises the following steps: (1) 20 mg of PTCDA raw powder was mixed with 5 mL of dimethylformamide (DMF) and ultrasonicated for 30 min; (2) Centrifuge at 8000 rpm for 30 minutes to remove water from MXene / H2O with a MXene content of 16 mg, then mix 5 mL of DMF with MXene and shake well, centrifuge for 5 minutes to remove DMF, and repeat three times to completely remove the water molecules to obtain MXene / DMF; (3) The materials of step (1) and step (2) are mixed and ultrasonically dispersed, and the resulting mixed solution is vacuum filtered using a 0.22 μm nylon filter membrane. After the filtration, the mixture is washed with deionized water and anhydrous ethanol for 3 to 5 times respectively, and then placed in a vacuum drying oven and dried at 40° C. for 1 hour.

[0021] (4) PTCDA / Ti3C2T obtained in step (3) x MXene powder was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 8:1:1, where PTCDA / Ti3C2T x The mass of MXene powder was 20 mg, 500 μL NMP was added, and then vortexed for 1 hour.

[0022] (5) Take 24 μL of the uniformly dispersed slurry obtained in step (4) and coat it on a 1 cm × 1 cm graphite paper so that the active material loading on each piece of graphite paper is 0.8 mg, and dry it in a vacuum drying oven at 40 ° C for 1 hour to obtain PTCDA / Ti3C2T x MXene anode.

[0023] In Example 1, PTCDA / Ti3C2T x SEM images of MXene are shown below: Figure 1 As shown in a, it shows its obvious intercalation structure, and its TEM image is as follows Figure 1 b, showing its thin layered structure. The rate curves of PTCDA and MXene at different ratios are shown in Figure 2. Figure 2 As shown, the optimal ratio is 6:4. x CV curves of MXene anode at different scan rates are shown in Figure 2. Figure 3 As shown in Figure 2, each CV curve has a similar shape and two pairs of obvious redox peaks, indicating the multi-step reversible Mn 2+ Ion embedding / de-embedding process. PTCDA / Ti3C2T x The GCD curves of MXene anode at different current densities are shown in Figure 2. Figure 4 As shown in the figure, the results show that there are two pairs of GCD platforms in the GCD curve, corresponding to a pair of redox peaks in the CV curve. x The energy storage mechanism of MXene / Mn battery system is as follows Figure 5 As shown, CuFe-TBA is used as the positive electrode, PTCDA / Ti3C2T x The full battery is composed of MXene as the negative electrode and 1 MMnSO4 as the electrolyte. Its energy storage mechanism is based on the Mn ion in PTCDA / Ti3C2T xInsertion / deinsertion of MXene anode (breaking and recovery of C=O bond). PTCDA / Ti3C2T x MXene anode at 10A g -1 The charge-discharge cycle stability curve at a current density of Figure 6 As shown in the figure, after 1000 cycles, the capacity can maintain 81.7% of the initial capacity, and the coulombic efficiency is close to 100%. Compared with pure PTCDA, the prepared aqueous manganese ion battery negative electrode material PTCDA / Ti3C2T x MXene has high reversible specific capacity and excellent cycling stability. Figure 7 PTCDA / Ti3C2T x The comparison of the coulombic efficiency of MXene and manganese metal (with manganese metal as the negative electrode, copper sheet as the positive electrode, and 1 M manganese sulfate as the electrolyte) shows that PTCDA / Ti3C2T x MXene has better Coulombic efficiency. Example 2

[0024] A negative electrode material PTCDA / Ti3C2T for aqueous manganese ion batteries x The preparation method of MXene is similar to that of Example 1, except that in step (4), PTCDA / Ti3C2T x The mass ratio of MXene powder, acetylene black and polyvinylidene fluoride is 6:2:2. Example 3

[0025] A negative electrode material PTCDA / Ti3C2T for aqueous manganese ion batteries x The preparation method of MXene is similar to that of Example 1, except that in step (4), PTCDA / Ti3C2T x The mass ratio of MXene powder, acetylene black and polyvinylidene fluoride is 7:2:1.

[0026] In the technical scheme of the present invention, although some numerical values ​​with better effects are given in the above embodiments, such as the ratio between PTCDA and MXene, the present invention is not limited to the ratio between PTCDA and MXene given in the above embodiments, and the specific ratio between PTCDA and MXene is determined according to actual needs; for example, the oscillation time of the slurry in the vortex oscillator with better effects is given in the embodiments, but the present invention is not limited to the oscillation time in the vortex oscillator given in the above embodiments, but the time should not be too short, and the specific oscillation time is determined according to actual needs; that is, the content claimed for protection of the present invention is based on the scope recorded and explained in the claims.

[0027] It should be noted that the above-described embodiments of the present invention are only explanations and clarifications for those skilled in the art to understand the technical essence of the present invention, so the technical contents described are not intended to limit the substantial protection scope of the present invention. The substantial protection scope of the present invention shall be subject to the claims. Those skilled in the art should know that any modifications, equivalent substitutions and improvements based on the substantial spirit of the present invention shall be within the substantial protection scope of the present invention.

Claims

1. PTCDA / Ti3C2T x The application of MXene as an anode material for aqueous manganese ion batteries is carried out by a method comprising the following steps: PTCDA / Ti3C2T x MXene is made into slurry and coated on the electrode and dried as the negative electrode of the battery; The PTCDA / Ti3C2T x MXene is synthesized via electrostatic self-assembly.

2. The use according to claim 1, characterized in that The PTCDA / Ti3C2T x MXene is prepared by the following method: Step (1): PTCDA raw powder is mixed with dimethylformamide (DMF) and ultrasonicated for 10-40 minutes; Step (2): remove water from MXene / H2O by centrifugation at a speed of 6000-10000 rpm for 10-40 minutes, then mix DMF and MXene and shake them well, and centrifuge to remove DMF; then add DMF and MXene and mix them well, and centrifuge to remove DMF, and repeat the DMF treatment to fully remove water to obtain MXene / DMF; Step (3): ultrasonically disperse the products obtained in step (1) and step (2) to obtain a mixed solution, and vacuum filter, wash and dry the obtained mixed solution.

3. The use according to claim 2, characterized in that In the step (1), the ratio of the mass of the original PTCDA powder to the volume of DMF is 18-22:4-6, mg / mL; preferably 20:5, mg / mL.

4. The use according to claim 2, characterized in that In the step (2), the ratio of the mass of MXene in the MXene / H2O liquid to the volume of DMF added each time is 15-20:4-6, mg / mL; preferably 16:5, mg / mL.

5. The use according to claim 2, characterized in that The mass ratio of the PTCDA original powder to MXene is 2-8:2-8, preferably 5-7:3-5, and more preferably 6:

4.

6. The use according to claim 2, characterized in that The filter membrane used for vacuum filtration in step (3) is a 0.22 μm nylon membrane, which is washed 3-5 times with deionized water and anhydrous ethanol respectively, and the drying temperature is 40-45° C. and the drying time is 1 hour.

7. The use according to claim 1, characterized in that PTCDA / Ti3C2T x MXene is made into slurry by mixing PTCDA / Ti3C2T x MXene was mixed with acetylene black, polyvinylidene fluoride, and NMP and then vortexed in a vortex shaker.

8. The use according to claim 7, characterized in that PTCDA / Ti3C2T x The mass ratio of MXene, acetylene black and polyvinylidene fluoride is (4-8):(1-3):(1-3). When PTCDA / Ti3C2T x When the mass of MXene powder is 15-25 mg, the volume of NMP is 500 μL.

9. An aqueous manganese ion battery comprising PTCDA / Ti3C2T x MXene negative electrode, CuFe-TBA positive electrode and Mn 2+ Ion electrolyte; the PTCDA / Ti3C2T x MXene negative electrode is PTCDA / Ti3C2T x MXene is made into a slurry and coated on an electrode and dried as a negative electrode of a battery. The PTCDA / Ti3C2T x MXene is synthesized via electrostatic self-assembly.

Citation Information

Patent Citations

  • Two-dimensional carbide crystal-based polyimide sodium-electric composite material as well as preparation method and application thereof

    CN111244418A

  • High-performance potassium ion battery organic conjugated carbonyl negative electrode and preparation method thereof

    CN118448563A